2014
DOI: 10.21916/mlr.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

The development of questions on disability for the Current Population Survey

Abstract: 8:45 am] Billing code 3195-01-P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Finally, overreporting of educational level in questionnaires due to misunderstanding has been reported [ 21 , 22 ]. It has been suggested that this misunderstanding is linked to the question regarding the duration of education (total years of education versus highest obtained degree) [ 21 , 22 ], and misclassification can occur when inferring attainment of a degree from years of schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, overreporting of educational level in questionnaires due to misunderstanding has been reported [ 21 , 22 ]. It has been suggested that this misunderstanding is linked to the question regarding the duration of education (total years of education versus highest obtained degree) [ 21 , 22 ], and misclassification can occur when inferring attainment of a degree from years of schooling.…”
Section: Discussionmentioning
confidence: 99%
“…The questions were validated in the National Comorbidity Survey, which demonstrated that the six measures used captured a high fraction of individuals with disabilities (US Census Bureau, 2019). Following this testing, disability questions were added to the Current Population Survey with slight modifications to further improve their ability to measure disabilities (McMenamin & Hipple, 2014). Our calculations indicate that the prevalence of difficulty due to a disability of adolescents in the ATUS was similar to the prevalence found in adolescents in the final month-in-sample in the Current Population Survey, which suggested the ATUS provided reliable information on youth disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, organizations using NCHPAD-adapted PPSEs or resources measure success through the increased participation of people with disability in community settings, and when applicable or able, improvements in health. At the programmatic level, the identification of participation of people with disabilities involves advising organizations to add one or two questions that serve as disability identifiers, such as the six disability questions used in the American Community Survey [ 38 ].…”
Section: Methodsmentioning
confidence: 99%